2022
DOI: 10.1109/access.2022.3210960
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Transformation Analysis of Capacitive Wireless Charging

Abstract: This paper studies the capacitive coupling in a capacitive power transfer (CPT) system designed for charging applications. It proposes mathematical models using the conformal transformation for calculating air-gapped and underwater capacitance and verifies the proposed models using COMSOL multiphysics and measurements. The measurement results show that we can achieve nano-farad capacitance ranges if we submerge the capacitor in seawater. The seawater's capacitance slightly changes when we increase the gap dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The output power and efficiency are not changing significantly with the changing of the separation distance between the transmitter and receiver couplers. When the separation distance increase from 50 mm to 500 mm, the efficiency increases from 43.5% to 44.7% while the output power decreases from about 30 W to 27 W. The enhancement in the efficiency is attributed to the decrease of the coupling conductance, and hence the parameter χ 2 , with the increase of the separation distance as explained in [18].…”
Section: Resultsmentioning
confidence: 82%
“…The output power and efficiency are not changing significantly with the changing of the separation distance between the transmitter and receiver couplers. When the separation distance increase from 50 mm to 500 mm, the efficiency increases from 43.5% to 44.7% while the output power decreases from about 30 W to 27 W. The enhancement in the efficiency is attributed to the decrease of the coupling conductance, and hence the parameter χ 2 , with the increase of the separation distance as explained in [18].…”
Section: Resultsmentioning
confidence: 82%
“…The fringing is the nonuniform distribution and the bending of electric fields near the edges. Several analytical and numerical models tried to calculate the capacitance considering the fringing effects [36]. The fringing fields can couple the plates with the ground or any charged object in proximity, leading to the formation of stray and parasitic capacitors.…”
Section: A Fundamental Operation Principlementioning
confidence: 99%
“…The salinity of seawater can increase the coupling capacitance. But it also causes a dielectric loss that degrades the overall efficiency of the system [12], [13], [36].…”
Section: B Design Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, studies can be found on dielectric properties of water or skin and their behavior in a CPT system. However, these kind of studies are limited to low power transfer of less than 130 W [14][15][16][17]. Despite the profound knowledge on dielectric materials for capacitors, to the best knowledge of the authors, little is known about media different from air for CPT applications with 100 W or more.…”
Section: Introductionmentioning
confidence: 99%